About the Necessity of a Comprehensive Evaluation of the Transportation System - Ullrich Martin (Promet - Traffic&Transportation, 1970)
A brief review is given of the current ideas about /raffle restrictionsand cost of traffic distribution systems including thecontroversy of individual and public transport under both privateand public regime.